2016
DOI: 10.1111/gcbb.12327
|View full text |Cite
|
Sign up to set email alerts
|

Range and uncertainties in estimating delays in greenhouse gas mitigation potential of forest bioenergy sourced from Canadian forests

Abstract: Accurately assessing the delay before the substitution of fossil fuel by forest bioenergy starts having a net beneficial impact on atmospheric CO 2 is becoming important as the cost of delaying GHG emission reductions is increasingly being recognized. We documented the time to carbon (C) parity of forest bioenergy sourced from different feedstocks (harvest residues, salvaged trees, and green trees), typical of forest biomass production in Canada, used to replace three fossil fuel types (coal, oil, and natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
46
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 46 publications
6
46
0
1
Order By: Relevance
“…In the case of perennial crops and forest systems, the main sources of uncertainty relate to carbon sequestration, soil carbon content, management practices and local climatic conditions. Additionally, timeframes when the carbon is sequestered and released play an important part in evaluating the real level of emissions [7,8]. In the biomass processing stage aspects such as drying, GHG emissions during storage and handling losses are major sources of emission uncertainties [8,25].…”
Section: Challenges Of the Real Ghg Reduction Potential Of Bioenergy mentioning
confidence: 99%
See 4 more Smart Citations
“…In the case of perennial crops and forest systems, the main sources of uncertainty relate to carbon sequestration, soil carbon content, management practices and local climatic conditions. Additionally, timeframes when the carbon is sequestered and released play an important part in evaluating the real level of emissions [7,8]. In the biomass processing stage aspects such as drying, GHG emissions during storage and handling losses are major sources of emission uncertainties [8,25].…”
Section: Challenges Of the Real Ghg Reduction Potential Of Bioenergy mentioning
confidence: 99%
“…Various recent assessments, in particular of forest-based bioenergy systems, have shown that the emission profiles can range widely depending on the methodological choice of the assessment and included factors. These factors were mainly related to aspects such as type and location of the forests, albedo changes after harvesting, level of climate intensity, harvest frequency, rotation length, conversion technology or type of systemic feedback and direct and indirect impacts [5][6][7][34][35][36]. This and above named factors show the challenges related to natural variability, supply chain and activity characteristics, wider often indirect impacts and methodological choices.…”
Section: Challenges Of the Real Ghg Reduction Potential Of Bioenergy mentioning
confidence: 99%
See 3 more Smart Citations